Boardroom gender diversity: implications for corporate sustainability disclosures in Malaysia - Zahid, Muhammad; Qureshi, Muhammad Imran; Haseeb, Ur Rahman; Ali, Wajahat; Khan, Musa; Alharthi, Majed D.; Jan, Amin (Elsevier Ltd., 2020)
This study aims to examine the impact of boardroom gender diversity, Malaysian Code on Corporate Governance (MCCG, 2012), and firms’ specific characteristics such as age, size, and profitability, on corporate sustainability disclosures (CSD) in Malaysia. The study applied Ordinary Least Square (OLS) to a stratified random sample composed of 878 public listed companies. These companies were selected in 11 sectors of the Malaysian economy for three years i.e. 2011 to 2013. The selection of time period has a rationale that Malaysia is mostly focused on improving both the corporate sustainability and representation of women directors on the board during this time. The results indicate that women directors have an imperative role in improving CSD as evident by their significant positive association with workplace and social, environmental, and economic dimensions of corporate sustainability. In addition, the comparison of findings in pre and post contexts of MCCG 2012, it is noted that the association between boardroom gender diversity and CSD has pronounced after enactment of the code. The findings are important, particularly in connection with a fast-growing and emerging economy like Malaysia. The findings have important insights for various stakeholders i.e. government, regulatory bodies, practitioners, academia, industry, and researchers